ANALYSIS OF THE EFFECTIVENESS OF PUBLIC SPEAKING SUBJECT MODULE INFORMATION-TECHNOLOGY (IT) BASED - Nafisah Endahati; Edy Purwanto (Ahmad Dahlan Journal of English Studies, 2016)
Public speaking is one of subjects must be attended by students of English Education Study Program. Several constrains were faced by students in performing public speaking. They were related to the limited learning tools and media, teaching methodology, and learning module. This research aims to analyze the effectiveness of public speaking subject module based on IT (Information Technology) applied in public speaking class of students of English Education Study Program, Faculty of Teacher Training and Education, PGRI University of Yogyakarta. The module which was applied in public speaking subject used a media learning based on IT.This quantitative research consisted of four procedures. The procedures done were defining, designing, developing, and disseminating. The participants were the students of English Education Study Program, Faculty of Teacher Training and Education, PGRI University of Yogyakarta. The data were collected through questionnaires to validate the module, to measure the practicability of the module, and to measure the effectiveness of the module. The module validity and practicability were analyzed qualitatively. Meanwhile, the effectiveness of the module was represented quantitatively.The research has been done. Module of public speaking subject is written well. The media for public speaking activity is represented into three themes. Each theme consists of four main activities. The first is listening activity. The second is giving opinion followed by comprehension task. The last activity is pronunciation task. The research test shows that the enthusiasm mean of using non based-IT media is 22, 33. The enthusiasm mean of using based-IT media is 27, 07. Based on the result of the test it can be concluded that using media based on IT is more valid, effective, and practical than using non-based IT media. It is because using media based on IT can fulfill students’ needs and can enhance students’ interest through learning material.